Turn‐On Photocatalysis: Creating Lone‐Pair Donor–Acceptor Bonds in Organic Photosensitizer to Enhance Intersystem Crossing - Mingjie Liu; Junnan Liu; Kai Zhou; Jingwen Chen; Qi Sun; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; Zhiguo Zhang (Advanced Science, 2021)
Abstract There is growing interest in developing triplet photosensitizers in terms of implementing photochemical strategies in synthetic chemistry. However, synthesis of stable triplet organic photosensitizers is nontrivial and often requires the use of heavy atoms. Herein, an alternative strategy is demonstrated to enhance the triplet generation efficiency by implanting lone‐pair donor–acceptor bonds in the conjugated covalent organic frameworks (COFs). This powerful method is validated using COFs that host triazine, a moiety that has been extensively investigated in photocatalysis. Spectroscopic analysis and theoretical calculations reveal substantial improvements in the photoabsorptivity and triple‐state photogeneration efficiency, consistent with catalytic tests concerning industrially relevant sulfide oxidation. These systems represent a promising addition to the rapidly increasing arsenal of synthetic photocatalytic systems.